Design, synthesis and insecticidal activity of novel analogues of flubendiamide containing alkoxyhexafluoroisopropyl groups. Issue 57 (17th September 2020) - Zhao, Xianghu; Xu, Sixue; Liu, Chuan; He, Jingjing; Li, Chunmei; Deng, Yupian; Cao, Song
Abstract : A series of novel analogues of flubendiamide bearing alkoxyhexafluoroisopropyl moiety was synthesized. Their insecticidal activities against various insects were evaluated. Abstract : Flubendiamide has received considerable attention in the agriculture field due to its novel mode of action and excellent insecticidal activity. However, the high cost and toxicity to aquatic invertebrates associated with flubendiamide limit its agronomic utility. On the basis of the structure of the lead compound, flubendiamide, we designed and synthesized a series of novel analogues of flubendiamide bearing a alkoxyhexafluoroisopropyl moiety using 2-methyl-4-(2-alkoxyhexafluoroisopropyl) anilines as the key intermediates. Their insecticidal activities against the oriental armyworm ( Mythimna separata Walker) were evaluated. The results indicated that most of the target compounds exhibited high insecticidal activities. Specifically, compound 8h showed the best insecticidal activity against the armyworm and its insecticidal activity reached 70% at 0.156 mg L −1 . The LC50 value of compound 8h (0.0512 mg L −1 ) is nearly the same as the corresponding commercial product flubendiamide (0.0412 mg L −1 ). Furthermore, the acute toxicity test showed that the 48 h LC50 values of compound 8h and flubendiamide against Daphnia magna Straus were 0.0066 and 0.0021 mg L −1, respectively. The toxicity of compound 8h is obviously lower than flubendiamide.